A functional polymorphism in the NAD(P)H oxidase subunit CYBA is related to gene expression, enzyme activity, and outcome in non-Hodgkin lymphoma. - Hoffmann, M.; Schirmer, M. A.; Tzvetkov, M. V.; Kreuz, M.; Ziepert, M.; Wojnowski, L.; Kube, D.; Pfreundschuh, M.; Trumper, L.; Loeffler, M.; Brockmoller, J. (Cancer Res, 2010)
NAD(P)H oxidase is a major endogenous source of reactive oxygen species (ROS). ROS may not only be involved in carcinogenesis but also in efficacy of chemotherapeutic agents like doxorubicin. By a comprehensive genotyping approach covering 48 genetic polymorphisms (single-nucleotide polymorphisms) in five subunits of phagocytic NAD(P)H oxidase, we asked whether they affect gene expression, enzymatic activity, and outcome of CHO(E)P chemotherapy. A highly consistent effect was observed for the CYBA 640A>G variant. In peripheral blood granulocytes of 125 healthy volunteers, the G allele of 640A>G was associated with lower NAD(P)H oxidase activity (P = 0.006). Moreover, the G allele was associated with lower mRNA and protein expression (both P = 0.02). Of clinical importance, the outcome of patients suffering from non-Hodgkin lymphoma and treated with CHO(E)P regimen was dependent on the CYBA 640A>G polymorphism. In an exploratory study (n = 401), carriers of 640GG had an event-free survival (EFS) risk ratio of 1.95 [95% confidence interval (95% CI), 1.31-2.90; P = 0.001] compared with 640AA. In a confirmatory set (n = 477), the risk ratios were 1.53 (1.04-2.25, P = 0.03). The complete set of 878 patients showed a relative risk of 1.72 (1.30-2.26) and 1.59 (1.14-2.21) for EFS and overall survival, respectively. Further molecular-biological experiments showed lower expression and reduced stability of transcripts with the G allele in lymphoblastoid cell lines. Transfection of allele-specific plasmids into HEK293 cells elicited lower activity for the G allele in a luciferase reporter gene construct. Thus, CYBA 640A>G was shown to be a functional polymorphism with possible consequences for patients receiving CHO(E)P chemotherapy and might have further implications for other ROS-mediated modalities.
Keywords: Adolescent; Adult; Antineoplastic Combined Chemotherapy Protocols/administration & dosage/therapeutic use; Cyclophosphamide/administration & dosage; Doxorubicin/administration & dosage; Etoposide/administration & dosage; Female; Gene Expression; Humans; Lymphoma, Non-Hodgkin/drug therapy/*enzymology/genetics; Male; Middle Aged; NADPH Oxidases/biosynthesis/*genetics/metabolism; Polymorphism, Single Nucleotide; Prednisolone/administration & dosage; Protein Subunits; RNA, Messenger/biosynthesis/genetics; Treatment Outcome; Vincristine/administration & dosage; Young Adult